Model Sebaran Dan Pemetaan Pembangunan Infrastruktur Kabel Fiber Optik Bawah Tanah Dengan Pendekatan SIG Di Kota Surabaya - M.Ferry Suryazain; Ronny Durrotun Nasihien; Julistyana Tistogondo (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
Surabaya City has an area of 33,306.30 Hectares and is divided into 31 sub-districts 154 villages and other government work units, known as SKPD (Satuan Kerja Perangkat Daerah). Regional devices provide services to the community, in order to support this, an internet network and supporting devices are needed which are connected to the network infrastructure between SKPD or public areas. This network infrastructure is managed and built by DINKOMINFO (Dinas Komunikasi dan Informatika) Surabaya City. The Surabaya City Government until 2022, has a total length of fiber optic cable installed in Surabaya reaching 285,932.74 meters as well as thousands of supporting devices such as CCTV and network device boxes. However, manual mapping and data collection methods have limitations in efficiency and accuracy. For this reason, a digital map using Geographic Information System (GIS) with ArcGIS application is required. Digital mapping enables more detailed and accurate geographic data collection, storage and analysis. Genteng sub-district will be the object of research because it has the highest density of fiber optic lines, with a total of 119 cable lines with a length of 21,383.7 meters or 21.4 kilometers, 74 access points, 31 handhole points and 127 CCTV points. This research produces a distribution map with the nearest neighbor method including an access point distribution map with a value of 1.0 which means a random distribution model, a handhole distribution map with a value of 1.6 uniform distribution models and, a CCTV point distribution map with a value of 0.7 group distribution models. The results of this research are expected to help in understanding the importance of digital map creation in network infrastructure development.